The wrecker [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Isaac Bell novels, 2009)
In 1907, after a rash of vandalism and sabotage, the Southern Pacific Railroad employs the famed Van Dorn Detective Agency. Charged with discovering the culprits behind the railroad's latest misfortune, the agency sends their best investigator, Isaac Bell, to the Cascades. However, after conversing with several drifters, Bell discovers that a man known as 'the Wrecker' is behind the random acts of violence.